Pemanfaatan Microsoft Excel Sebagai Perangkat Pengembangan Prototipe Piranti Lunak Visual - Ivransa Zuhdi Pane (ULTIMA InfoSys, 2015)
Software prototype is a simplified form of the real software which is developed to assist the upstream engineering activities. Developing the prototype is especially of importance in gathering the requirement and modeling the main functionalities of the software. Among tools available to prototype the software, Microsoft Excel, with its advantageous spreadsheet features and considerable popularity, is worthy to be considered as an alternative candidate. Several case studies are explored to show the usefulness of Microsoft Excel as a prospective tool in prototyping the visual softwares. Index Terms - prototype, software engineering, visual software.